Contemporary Interpretation Methodology: Comparative Study of the Thought of Fazlur Rahman and Sahiron Syamsuddin - Hendri, Jul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This article discusses Contemporary Interpretation Methodology (Comparative Study of the Thoughts of Fazlur Rahman and Sahiron Syamsuddin). The background is related to contemporary interpretations that exist in today's society. The aim is to provide an explanation of the comparison of two contemporary figures, namely Fazlur Rahman and Sahiron Syamsuddin. By using library research methods. This research was carried out by researching and analyzing based on library sources. The discussion is explained descriptively (outlining the sources obtained and then analyzed). The books used are secondary sources enriched from various other literary sources. The results of the research concluded that Fazlur Rahman with his theory of double movement. And Sahiron Syamsuddin with the ma'na cum maghza theory.